Monitoring Fluorinated Dendrimer‐Based Self‐Assembled Drug‐Delivery Systems with 19F Magnetic Resonance. Issue 30 (15th August 2017) - Liu, Xin; Yuan, Yaping; Bo, Shaowei; Li, Yu; Yang, Zhigang; Zhou, Xin; Chen, Shizhen; Jiang, Zhong‐Xing
Abstract : Monitoring a drug‐delivery system with an imaging modality is of great importance for detailed understanding of drug‐delivery processes and for achieving optimal therapeutic effects. Here, novel fluorinated self‐assembled dendrimers with a single 19 F NMR signal were conveniently synthesized on multigram scales, and 19 F magnetic resonance, including spectroscopy ( 19 F NMR) and imaging ( 19 F MRI), was used to monitor the fluorinated dendrimer‐based self‐assembled drug‐delivery systems. It was found that 19 F NMR and 19 F MRI were convenient and sensitive tools to monitor the self‐assembly and drug‐loading processes and to detect weak interactions between the drug and the drug‐delivery vehicle because changes in the self‐assembly profile sensitively induced corresponding 19 F magnetic resonance responses. Abstract : Monitoring drug‐delivery systems with an imaging modality is of great importance to achieve optimal therapeutic effects. Here, 19 F magnetic resonance is used as a convenient and sensitive tool to monitor self‐assembled drug‐delivery systems because changes in the self‐assembly profile sensitively induce corresponding 19 F magnetic resonance responses.